Singapore budget 2015: Building our future, strengthening social security - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2015)
Our Budget for FY2014 is expected to record a slightly smallerdeficit than what we had estimated a year ago. We had budgetedfor an overall deficit of $1.2 billion (or 0.3% of GDP). We nowexpect a very small deficit of $0.1 billion, close to a balancedposition.